Neuro-oncology clinicians' perspectives on factors affecting brain cancer patients' access to medical assistance in dying: A qualitative study. Issue 3 (16th March 2023) - Variath, Caroline; Climans, Seth A.; Edelstein, Kim; Bell, Jennifer A. H.
Abstract: In most jurisdictions where medical assistance in dying (MAiD) is legal, patients must have decision-making capacity. Brain cancer often damages the cognitive networks required to maintain decision-making capacity. Using qualitative methodology guided by a relational ethics conceptual framework, this study explored neuro-oncology clinicians' perspectives on access to and eligibility for MAiD for patients diagnosed with brain cancer. We interviewed 24 neuro-oncology clinicians from 6 countries. Participants described the unique challenges facing brain cancer patients, potentially resulting in their inequitable access to MAiD. The findings highlight the importance of early end-of-life conversations, advance care planning, and access to end-of-life treatment options.